Unemployment Insurance, Unemployment Duration, and Excess Supply of Labour - Maki, Dennis (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
This paper examines the effect of the unemployment insurance scheme on the duration of unemployment spells in Canada in the period 1953-1973.